Javanese ethnomathematics: Exploration of the Tedhak Siten tradition for class learning practices - Wiryanto; Primaniarta, M. Gita; Mattos, Roberto Linhares de (Journal on Mathematics Education, 2022)
Tedhak Siten is a Javanese traditional ceremony that marks the 8th month of the baby’s age, marked by the baby's readiness to set foot on the ground. This tradition has a philosophical meaning with Javanese cultural values related to the concepts of calculating the ceremony time and the geometric shape of the ceremonial equipment used. The purpose of this study was to explore the cultural activities of the Javanese community by outlining the mathematical concepts contained in the implementation of the Tedhak Siten ceremony. This research was a qualitatively descriptive study through an ethnographic approach. Ethnomathematical data were collected from two experts those were the head of a traditional Javanese culture studio and a cultural actor active as a leader of Javanese traditional ceremonies. The ethnomathematics found in the study were counting the date or time for the implementation of the Tedhak Siten tradition and the elaboration of geometric concepts in the form of ceremonial equipment used to perform traditional customary procedures. This research had an impact as a mathematics learning material that originated from the wisdom of the local Javanese community by applying the concepts of time units, least common multiples, modulo 5, modulo 7, circles, triangles, rectangles, cylindrical volumes and spherical volumes.